Development of Shelf Stable Edible Product from Sheep Rumen - P. S., Girish; Ramakrishna, C.; Reddy, P. Baswa; Chalasani , Vijay Kumar; Babji , Y. (Journal of Meat Science, 2012)
Sheep (Ovis aries) belongs to the ruminant classification of animal. Ruminants are characterized by presence of four stomachs viz., rumen, reticulum, omasum and abomasums. Rumen is the largest part of four stomachs of ruminants. Due to rubbery texture rumen is not preferred for consumption by consumers. This work was undertaken to develop a shelf stable value added product named as ‘sheep rumen crackle’ for profitable utilization of sheep rumen. Steps in production of sheep rumen crackle include collection of sheep rumen, cleaning, cutting, cooking, addition of salt & spices and drying to reach a moisture level of 5.30 ± 0.13 % and a water activity of 0.32 ± 0.01. Levels of salt and spices were standardized at 3.0 % and 1.0 % respectively. Dried rumen flakes are semi convenient products which can be stored at room temperature and can be fried before consumption. Fried products are shelf stable and could be stored by aerobic packaging at room temperature up to one year. No microbial growth including total plate count, coliforms and yeast & mould count were found in the product even after one year storage. Products were highly acceptable by the sensory panel and crispiness of the products enhanced its acceptability. It was concluded that preparation of sheep rumen crackles can be an effective approach for profitable utilization of sheep rumen.
Keywords: Sheep; byproduct; rumen; dried product; shelf stable; crackles